Radiotherapy combined with immunotherapy successfully treated one case of anaplastic thyroid cancer: A case report - Xing, Yurou; Wang, Yongsheng; Wu, Xin (Frontiers in Oncology, 2023)
Background: Anaplastic thyroid cancer (ATC) is a rare but highly fatal form of thyroid cancer. This highly malignant tumor progresses rapidly and is prone to relapse and metastasis, with a poor prognosis. Novel treatments have improved survival in recent years, but the outcome of treatment is not satisfactory. Case Presentation:We report a case of multiple postoperative recurrences of papillary thyroid carcinoma that later transformed into undifferentiated carcinoma. The patient’s neck mass was huge and operation was unsuitable. Then, she obtained remarkable tumor shrinkage by tislelizumab immunotherapy combined with radiotherapy. Conclusion: This case indicate that radiotherapy combined with immunotherapy is a promising treatment for ATC. Such a combined approach warrants further study.